Antioxidant potential of coenzyme Q10 in Escherichia coli associated calf diarrhea - GARKHAL, J; CHETHAN, G E; GUPTA, V K; QURESHI, S; MUKHERJEE, R; DIMRI, U; GAUR, G K; AGARWAL, R K; DE, U K (The Indian Journal of Animal Sciences, 2017)
The aim of the present study was to evaluate the antioxidant potential of coenzyme Q10 in Escherichia coli associated calf diarrhea. Six diarrheic calves were treated with standard treatment (ST) and another six diarrheic calves were given standard treatment along with coenzyme Q10 (ST-CoQ10). Whereas, six healthy calves received only placebo. The results revealed a significant reduction of Hb, PCV, TLC, albumin, BUN, creatinine, oxidative stress indicators, IFABP2, fecal consistency score and dehydration (%) in diarrheic calves treated with either ST or ST-CoQ10 on day 3 and 5. However, ST-CoQ10 treatment effectively reduced the oxidative stress indicators and IFABP 2 much earlier (day 3) compared to ST treatment alone. The results of the present study suggest that the incorporation of CoQ10 in standard treatment represents a potential additional treatment option in the case of E. coli associated calf diarrhea.